Alcohol reduction in red wines by technological and microbiological approaches: a comparative study. (17th August 2017) - Rolle, L.; Englezos, V.; Torchio, F.; Cravero, F.; Río Segade, S.; Rantsiou, K.; Giacosa, S.; Gambuti, A.; Gerbi, V.; Cocolin, L.
Abstract: Background and Aims: The aim of this work was to assess and compare the chemical composition and colour characteristics of Barbera red wines obtained after partial alcohol reduction using three promising methodologies for implementation at the industrial level. Methods and Results: Alcohol reduction was achieved by: (i) pre‐fermentation addition of liquid derived from grape must (reverse osmosis by‐product); (ii) mixed fermentations with strains of Starmerella bacillaris and Saccharomyces cerevisiae ; and (iii) dealcoholisation of wine post‐fermentation with a polypropylene membrane. The microbiological approach enabled the production of wines with a slightly lower alcohol concentration (−0.2 to −0.3% v/v), while facilitating the release of anthocyanin and some esters of fatty acids (ethyl hexanoate and ethyl dodecanoate) that could contribute positively to wine aroma with pleasant nuances. The low impact of the partial replacement of grape juice on the chemical composition and chromatic characteristics of Barbera wines makes this technique a good option for reducing the ethanol concentration by up to 1.0–2.0% v/v. In contrast, the use of a polypropylene membrane influenced negatively the composition of red wines by reducing significantly the concentration of esters (−60%) and anthocyanin (−17%), independently of the dealcoholisation level (up to −2% v/v). Conclusions: The alcohol reduction strategies can greatly influence the volatile and phenolic composition of the wine. The choice of either a technological or microbiological approach in the wine industry is dependent on the alcohol reduction required. Significance of the Study: This is the first comparative study of three strategies to reduce the alcohol concentration on the same batch of must/wine.